A critical evaluation of glucocorticoids in the management of severe COVID-19. (August 2020) - Solinas, Cinzia; Perra, Laura; Aiello, Marco; Migliori, Edoardo; Petrosillo, Nicola
Graphical abstract: Physiology and pathophysiology of pulmonary alveoli during SARS-CoV-2 infection. (A) COVID-19 severity: frequency of degrees of clinical manifestations in a Chinese cohort (>44.000 patients) (ref: Wu Z. et al, 2020). (B) Phases of COVID-19 disease and timing for the use of glucocorticoids. Legend: ARDS: Adult Respiratory Distress Syndrome; COVID-19: CoronaVirus Disease-19; MOF: multi-organ failure; pts: patients; SIRS: systemic inflammatory response syndrome. Highlights: Dexamethasone reduces the risk of death in patients critically ill with COVID-19. No evidence of benefit from other complementary and/or supportive treatments was seen in critically ill COVID-19 hospitalized patients. Synthetic glucocorticoids switch off cytokine storm, and consequent severe respiratory and multi-organ failures in patients with COVID-19. Effects of synthetic glucocorticoids might be confounded by the contemporary use of other complementary drugs. Abstract: The viral infection by SARS-CoV-2 has irrevocably altered the life of the majority of human beings, challenging national health systems worldwide, and pushing researchers to rapidly find adequate preventive and treatment strategies. No therapies have been shown effective with the exception of dexamethasone, a glucocorticoid that was recently proved to be the first life-saving drug in this disease. Remarkably, around 20 % of infected people develop a severe form of COVID-19, giving rise to respiratory and multi-organ failures requiring subintensive and intensive care interventions. This phenomenon is due to an excessive immune response that damages pulmonary alveoli, leading to a cytokine and chemokine storm with systemic effects. Indeed glucocorticoids' role in regulating this immune response is controversial, and they have been used in clinical practice in a variety of countries, even without a previous clear consensus on their evidence-based benefit.